Optimized low-power CMOS active-electrode-pair for low-frequency multi-channel biomedical stimulation. (August 2017) - Al-Darkazly, Ibtisam A. Abbas; Hasan, S.M. Rezaul
Abstract: A novel CMOS active electrode-pair for electro-bio- stimulation with high signal integrity is being reported in this paper. The active electrode employs a buffer circuit based on an adaptive voltage follower to increase the output current in an efficient way, while minimizing the overall power consumption. The active electrode-pair circuit was fabricated in a 130 nm CMOS process using a low supply-voltage of +1.2 V, consuming only 100.8 µW. It occupies a small chip-area of around 2936.23 µm 2 (2 × 1468.12 µm 2 ). It can deliver bi-phase square waveform signals from 16 selectable low-frequency channels. The individual active electrode can also be used to deliver mono-phase square waveform output signals. Being a miniature bioelectronic component, it is suitable both as an implantable and as non-invasive biomedical stimulation device.